Penerapan Metode Bercerita dalam Meningkatkan Kemampuan Bahasa Ekspresif - Saryanti Saryanti; Ulfah Amini; Mamah Rohmatussa’diyah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2023)
This research was motivated by initial observations at RA Al Manar Harjamukti Cirebon, children's expressive language skills still have difficulties. This condition can be seen when children are given the opportunity to respond when questioning and answering with the teacher and telling stories in front of the class are still shy and not confident. This study aims to determine the improvement of expressive language skills with storytelling methods in group B children of RA Al Manar Harjamukti Cirebon for the 2022/2023 academic year. This research is a Classroom Action Research. The subjects of this study were 18 people consisting of 9 boys and 9 girls. The study was conducted in two cycles. Each stage of the cycle consists of planning, execution, observation and reflection. The data collection technique used is by observation. The results showed an increase in children's expressive language skills with the storytelling method. This is shown from observational data in pre-cycle, cycle I and cycle II. In Pre-Cycle Action by 36.1%, it increased in cycle I to 43.5% and in cycle II it increased to 84.7%. The conclusion of this study is that the storytelling method can improve expressive language skills in group B RA Al Manar Harjamukti Cirebon children.